The Effect of Business Strategy, Market Orientation, and Innovation Capability on Vehicle Rental Business Firm Performance in Indonesia - Erlina Dwi Ratnasari; Leo Andri Yulius Caesar; Sarah Alia Djohan (Budapest International Research and Critics University, 2022)
The purpose of this study was to determine the effect of business strategy, market orientation, and innovation capability on firm performance. The object of this research is all permanent employees of XYZ firm Jakarta branch. The data collection technique is by distributing questionnaires to all permanent employees of XYZ firm as many as 43 respondents. This data analysis method uses multiple linear regression analysis using IBM SPSS 22. The results of this study show that business strategy has a positive and significant effect on firm performance, market orientation has a positive and significant effect on firm performance, innovation capability has a positive and significant impact on firm performance and business strategy, market orientation, innovation capability have a positive and significant impact on firm performance.